1999
DOI: 10.1002/(sici)1097-0029(19991215)47:6<401::aid-jemt4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central structures involved in insect gustation

Abstract: Studies in insect gustation have a long history in general physiology, particularly with work on fly labellar and tarsal sensilla and in the general field of insect-plant interactions, where work on immature Lepidoptera and chrysomelid beetles has been prominent. Much more emphasis has been placed on the physiological characteristics of the sensory cells than on the central cellular mechanisms of taste processing. This is due to the fairly direct access for physiological experimentation presented by many taste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 68 publications
1
78
0
Order By: Relevance
“…Although the sensory inputs and genetic pathways involved in D. melanogaster oviposition preference are relatively uncharacterized, the role of taste and olfaction in egg laying of other insects has been investigated (1,6,14,15). In addition, AA can be aversive to D. melanogaster in certain olfactory assays (5,16).…”
Section: Egg-laying Preference For and Positional Aversion To Aa-contmentioning
confidence: 99%
“…Although the sensory inputs and genetic pathways involved in D. melanogaster oviposition preference are relatively uncharacterized, the role of taste and olfaction in egg laying of other insects has been investigated (1,6,14,15). In addition, AA can be aversive to D. melanogaster in certain olfactory assays (5,16).…”
Section: Egg-laying Preference For and Positional Aversion To Aa-contmentioning
confidence: 99%
“…2E). Two additional groups of neurons labeled with GFP innervate the labral sense organs (LSO) (Stocker, 1994;Mitchell et al, 1999). This paired organ of the internal mouth parts is composed of six mechanosensory and eight chemosensory neurons (Singh, 1997), about six of which express GFP (Fig.…”
Section: Late Enhancer Active In Chemosensory Neurons Of All Taste Brmentioning
confidence: 99%
“…Axons project to the central nervous system and, in particular, those from labellar sensilla into the subesophageal ganglion, while those from tarsal sensilla into the thoracic-abdominal ganglion (Mitchell et al 1999;Wang et al 2004;Kwon et al 2014). Recently, Masala et al (2014) showed that labellar sensilla of the medfly contain four gustatory receptor neurons (GRNs), that responded to different stimuli like sodium chloride (NaCl) and fructose.…”
Section: Introductionmentioning
confidence: 99%